2020
DOI: 10.1186/s42834-020-00069-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (VI) tolerance and bioaccumulation by Candida tropicalis isolated from textile wastewater

Abstract: In the present study a yeast strain isolated from industrial wastewater, identified as Candida tropicalis, showed chromium (Cr) tolerance level up to 5 mM. Yeast grown in minimal salt medium containing Cr (VI) ions for 48 h and crude enzyme extracts were tested for chromate reductase activity. Optimum temperature and pH of chromate reductase were 30 °C and pH of 7. The enzyme activity was greatly enhanced in the presence of divalent metal cations. Total protein profile revealed some protein bands were present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The accumulation capacity of Cr 6+ by strain R‐MT1/YieF was considerably decreased by the presence of Ag +1 , Hg 2+ and Cd 2+ in the culture medium. This may due to the inhibitory effect of these metal ions on the activity of chromate reductase 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…The accumulation capacity of Cr 6+ by strain R‐MT1/YieF was considerably decreased by the presence of Ag +1 , Hg 2+ and Cd 2+ in the culture medium. This may due to the inhibitory effect of these metal ions on the activity of chromate reductase 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Resistance in yeast is mostly due to the limited Cr uptake, by direct transformation of Cr(VI) to Cr(III) or by secreting reducing agents that reduce Cr(VI). A yeast isolated from industrial wastewater (Candida tropicalis), showed the ability to uptake Cr(VI) and reduce it to Cr(III; Ilyas et al, 2020). The yeasts S. cerevisiae and Pichia guilliermondii were able to reduce Cr(VI) and produce a chelating agent that trapped Cr(III) extracellularly when grown in the presence of Cr(VI) (Ksheminska et al, 2006).…”
Section: Direct Resistance Mechanismsmentioning
confidence: 99%
“…The toxic effect of heavy metals on microorganisms is mediated, for example, by inhibition of enzyme activity or by alterations in protein synthesis and ATP production ( 21 ). There are practically non-existent data that show the levels of Cr (III) or Cr (VI) after the chemical or enzymatic hydrolysis of the wastes ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%